ANALISIS YURIDIS PENJATUHAN HUKUMAN TERHADAP PELAKU TINDAK PIDANA NARKOTIKA (Studi Putusan Nomor 235/Pid.Sus/2019/PN.Tar) - Fiktorius Kehidupan Dao (Jurnal Panah Hukum, 2022)
Narcotics are substances or drugs derived from plants or non-plants, both synthetic and semisynthetic which can cause decreased or altered consciousness, disappearance, reduce and eliminate pain and cause addiction. One of the narcotics crimes that have been examined and tried by the Tarakan District Court is decision number 235/Pid.Sus/2019/PN.Tar. The type of research used is normative legal research with an approach method, a statutory approach, a case approach, and an analytical approach. Data was collected using secondary data, which was obtained through library materials consisting of primary, secondary, and tertiary legal materials. The data analysis used was descriptive qualitative data analysis and conclusions were drawn using the deductive method. Based on the research findings and discussion, it can be concluded that the sentencing of narcotics criminals (decision study number 235/Pid.Sus/2019/PN.Tar), in terms of proof, it is clear that the elements in Article 114 paragraph (2 ) Law No. 35 of 2009 concerning Narcotics which was violated by the perpetrators has been fulfilled. The criminal imposition of the perpetrator is not in accordance with Article 114 paragraph (2) of Law Number 35 of 2009 concerning Narcotics, which is a minimum imprisonment of 6 (six) years and a maximum of 20 (twenty) years and a maximum fine as referred to in paragraph (1 ) plus 1/3 which is Rp. 13,330,000,000 (thirteen billion three hundred and thirty million rupiah). However, the judge's decision to hear the case only sentenced the perpetrator to 18 (eighteen) years in prison, without imposing a fine. The author suggests to law enforcers, the Panel of Judges who examines and decides on a Narcotics criminal case to be more careful in imposing penalties imposed on Narcotics criminals, adjusted to the applicable laws and regulations